Contextual Teaching and Learning Effectiveness on Critical Thinking Ability Based on Students’ Learning Styles - Fadhillah, Farah; Puspita, Mettatama Gandha (Future Space: Studies in Geo-Education, 2025)
The aim of this research is to find out whether there is effectiveness between the use of Contextual Teaching and Learning (CTL) with conventional learning has an effect on critical thinking skills based on learning styles, especially in disaster mitigation material in Geography lessons. This research was conducted at SMAN 1 Turen in Class XI IPS 3 which was used as an experimental group that applied the CTL model, while class The research method used is post-test only control group design, which is quasi-experimental research. Critical thinking abilities are measured by giving tests in the form of essay questions. The independent variable in this research is the CTL model, while the dependent variable is critical thinking ability and the moderate variable is learning style. Data was generated from administering tests and distributing questionnaires from 59 respondents. After the data was collected, the Friedman test was carried out as a statistical test because the data was not spread evenly. Significant results obtained 0.000 (this value is less than 0.05) in the Friedman test qualification based on learning style and posttest results, indicating rejection of HO while H1 accepted. The hypothesis proposed leads to the conclusion that, CTL learning is effective in improving critical thinking skills based on student learning styles.